Residential exposure to petroleum refining and stroke in the southern United States. (1st September 2022) - Kim, Honghyok; Festa, Natalia; Burrows, Kate; Kim, Dae Cheol; Gill, Thomas M; Bell, Michelle L
Abstract: The southern United States (US) sustains a disproportionate burden of incident stroke and associated mortality, compared to other parts of the US. A large proportion of this risk remains unexplained. Petroleum production and refining (PPR) is concentrated within this region and emits multiple pollutants implicated in stroke pathogenesis. The relationship between residential PPR exposure and stroke has not been studied. We aimed to investigate the census tract-level association between residential PPR exposure and stroke prevalence for adults (⩾18 years) in seven southern US states in 2018. We conducted spatial distance- and generalized propensity score-matched analysis that adjusts for sociodemographic factors, health behavioral factors, and unmeasured spatial confounding. PPR was measured as inverse-distance weighted averages of petroleum production within 2.5 km or 5 km from refineries, which was strongly correlated with measured levels of sulfur dioxide, a byproduct of PPR. The prevalence of self-reported stroke ranged from 0.4% to 12.7% for all the census tracts of the seven states. People with low socioeconomic status and of Hispanic ethnicity resided closer to petroleum refineries. The non-Hispanic Black population was exposed to higher PPR, while the non-Hispanic White population was exposed to lower PPR. Residential PPR exposure was significantly associated with stroke prevalence. One standard deviation increase in PPR within 5 km from refineries was associated with 0.22 (95% confidence interval: 0.09, 0.34) percentage point increase in stroke prevalence. PPR explained 5.6% (2.4, 8.9) of stroke prevalence in the exposed areas. These values differed by states: 1.1% (0.5, 1.7) in Alabama to 11.7% (4.9, 18.6) in Mississippi, and by census tract-level: 0.08% (0.03, 0.13) to 25.3% (10.6, 40.0). PPR is associated with self-reported stroke prevalence, suggesting possible links between pollutants emitted from refineries and stroke. The increased prevalence due to PPR may differ by sociodemographic factors.